Analysis of Influence Service Quality, Facilities and Level of Satisfaction in Returning Treatment - Tartilah Nur Amani; Sentot Imam Suprapto; Yuly Peristiowati (Indonesian Journal of Global Health Research, 2025)
Increasing the quality of service and supporting facilities will provide patient satisfaction. If patients are satisfied with the health services received, if the patient needs health services they will tend to be interested in making repeat visits to seek treatment at the Watukenongo Health Center. This study aims to analyze the effect of service quality, facilities and satisfaction levels on repeat visit interest at the Watukenongo Community Health Center. The research method uses a cross-sectional study design. This study was conducted at the Watukenongo Health Center outpatient clinic starting from January-February 2025. The sample in the study was 165 patients, namely new patients, general patients and patients who were in the Watukenongo Health Center area and received services. The sampling technique was simple random sampling. The data analysis method used was univariate analysis, chi square and multiple logistic regression tests. The results of the chi square test were that service quality (p value 0.0371 <0.05) had a significant effect on interest in visiting the Watukenongo Health Center, facilities (p value 0.009 <0.05) had a significant effect on interest in repeat visits, satisfaction (p value 0.005 <0.05) had a significant effect on interest in visiting the Watukenongo Health Center. From the results of the logistic regression test, namely, satisfaction with a p-value of 0.0043 and OR/ (Exp(B))= 2.217, facilities with a p-value of 0.0015 and OR/ (Exp(B))= 3.942, quality of health services with a p-value of 0.0016 and OR/ (Exp(B))= 4.436. The conclusion is that the quality of service, facilities and level of satisfaction affect the interest in revisiting the Watukenongo Health Center. However, for patients who feel satisfied, it is 4.436 times more influential in attracting interest in revisiting the Watukenongo Health Center.